Injury Patterns and Severity of Motorcycle Crash Injuries Among Hospitalized Children and Adolescents in Darab, Iran in 2016: A cross-Sectional Study - Parisa Navabi; Rahim Tahmasebi; Maryam Ravanipour (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Injuries caused by motorcycle crashes in children and adolescents are one of the main health problems that can cause serious injuries or even death in this population. Objectives: This study aimed to determine the injury patterns and severity of motorcycle crash injuries among hospitalized children and adolescents in Darab, Iran. Methods: This descriptive cross-sectional study was started on May 15, 2017 and continued for three months. All 212 children and adolescents, who had been injured in motorcycle crashes in 2016 and were referred to the emergency ward of the central hospital of Darab, were selected, and their medical records were reviewed. The data collection tools included a demographic information form, an injury-related questionnaire, and the Injury Severity Score (ISS). Data analysis was performed in SPSS v16, using descriptive statistics, Mann-Whitney test, and Chi-square test at a significance level of α≥0.05. Results: The mean age of the injured children was 14.28±2.97 years. The head was the most commonly injured organ, while 130 (61.3%) cases had been injured in more than one organ. Most children had minor injuries with an ISS<9 (79%). The highest frequency of accidents was reported in the summer and spring. The majority of the injured motorcycle riders (n=191, 90%) had not used a helmet. Besides, the use of helmet was found to decrease with advancing age (P=0.017).Conclusion: Although head injuries are more frequent than injuries to other parts of the body, and more than 90% of motorcyclists do not wear helmets, informing and educating children and families is very important in this area. It is recommended to implement strict traffic laws for motorcycling and highlight the necessity of wearing helmets by motorcycle riders. Moreover, families should be stricter about their children riding motorcycles, especially during school holidays (summer and spring).